2012
DOI: 10.1186/1741-7007-10-36
|View full text |Cite
|
Sign up to set email alerts
|

UBXN7 docks on neddylated cullin complexes using its UIM motif and causes HIF1α accumulation

Abstract: BackgroundThe proteins from the UBA-UBX family interact with ubiquitylated proteins via their UBA domain and with p97 via their UBX domain, thereby acting as substrate-binding adaptors for the p97 ATPase. In particular, human UBXN7 (also known as UBXD7) mediates p97 interaction with the transcription factor HIF1α that is actively ubiquitylated in normoxic cells by a CUL2-based E3 ligase, CRL2. Mass spectrometry analysis of UBA-UBX protein immunoprecipitates showed that they interact with a multitude of E3 ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 52 publications
7
77
1
Order By: Relevance
“…Such synergies can be caused by simultaneously disrupting two components of a protein complex (Pérez-Pérez et al, 2009;Lanctot et al, 2013). In addition, ubiquitin receptors have been reported to interact with E3 ubiquitin ligases and influence the degradation of their ubiquitinated substrates in animals (Alexandru et al, 2008;Bandau et al, 2012). We therefore assessed whether DA1 interacts with the E3 ubiquitin ligase DA2 using an in vitro interaction/ pull-down experiment.…”
Section: Da1 Interacts With Da2 In Vitro and In Vivomentioning
confidence: 99%
“…Such synergies can be caused by simultaneously disrupting two components of a protein complex (Pérez-Pérez et al, 2009;Lanctot et al, 2013). In addition, ubiquitin receptors have been reported to interact with E3 ubiquitin ligases and influence the degradation of their ubiquitinated substrates in animals (Alexandru et al, 2008;Bandau et al, 2012). We therefore assessed whether DA1 interacts with the E3 ubiquitin ligase DA2 using an in vitro interaction/ pull-down experiment.…”
Section: Da1 Interacts With Da2 In Vitro and In Vivomentioning
confidence: 99%
“…A study has identified hundreds of potential CRL targets, where functional inactivation of cullins was combined with genetic and proteomic approaches, displaying the diversity of CRLs to control protein stability (Emanuele et al 2011). Different models exist for the role of NEDD8 in the regulation of CRL function, including cullin dimerisation, dissociation of cullins from its negative regulator CAND1, conformational changes that bring the E3-RING ligases RBX1/2 in close proximity to the substrate protein, stabilisation of the active CRL state, or control the CRL binding with other E3-ligases and components of the p97 pathway (Duda et al 2008, Saha & Deshaies 2008, Merlet et al 2009, Deshaies et al 2010, Duda et al 2011, Bandau et al 2012, den Besten et al 2012, Kelsall et al 2013, Pierce et al 2013, Wu et al 2013, Zemla et al 2013.…”
Section: Substrates For Nedd8mentioning
confidence: 99%
“…Among these receptors, the UIM domain of Rpn10 has been most studied and is believed to bind Ub chains directly (56). Moreover, the UIM domain of another protein, UBXD7, has been shown to bind to conjugated Nedd8 on CUL2 (94,95). This inspired us to examine whether Rub1 and the Rub1-Ub heterodimer interact with the UIM domain of Rpn10.…”
Section: Rub1-ub Heterodimer Is Recognized By the Proteasome And Procmentioning
confidence: 99%